2014
DOI: 10.1177/2047487314564896
|View full text |Cite
|
Sign up to set email alerts
|

The predictive role of renal function and systemic inflammation on the onset of de novo atrial fibrillation after cardiac surgery

Abstract: Age and eGFR were identified as the strongest predictors of POAF in a population largely composed of valve surgery patients. Renal function, even from early stage, is independently associated with the increasing risk of developing POAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…First, the meta-analysis was based on data from study level rather than individual patient data. Accordingly, influences of a few key characteristics on the possible preventative role of Dex for POAF could not be analyzed in our meta-analysis, such as left atrial volume ( 44 ), renal function ( 45 ), and concurrent cardiovascular medications including perioperative use of beta-blockers, amiodarone, and electrolyte replacement protocol for K and Mg etc. ( 46 ), which have all been suggested to affect the risk of POAF after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…First, the meta-analysis was based on data from study level rather than individual patient data. Accordingly, influences of a few key characteristics on the possible preventative role of Dex for POAF could not be analyzed in our meta-analysis, such as left atrial volume ( 44 ), renal function ( 45 ), and concurrent cardiovascular medications including perioperative use of beta-blockers, amiodarone, and electrolyte replacement protocol for K and Mg etc. ( 46 ), which have all been suggested to affect the risk of POAF after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Recent studies have shown that CKD, even of a mild degree, is associated with the development of AF independent of traditional risk factors. 37 However, the underlying pathophysiological mechanisms of this association have not been fully elucidated. We found that CKD was significantly associated with impaired LA reservoir function in a general population without overt cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a global health concern 1,2 and is recognized as an independent risk factor for the development of atrial fibrillation (AF). 37 However, the underlying mechanisms for the higher incidence of AF in patients with CKD are not yet fully elucidated. Although left atrial (LA) enlargement is an established marker for the development of AF, recent studies have reported that impaired LA reservoir function preceded LA enlargement 8,9 and was strongly associated with the development of AF, independent of LA volume and left ventricular (LV) function.…”
Section: Introductionmentioning
confidence: 99%
“…C-reactive protein) have been reported in early stages of CKD, and inflammation plays a significant role in the pathogenesis of AF. 13,14 Neurohormonal activation has also been implicated in the pathogenesis of renal dysfunction and AF, with the activation of the renin-angiotension-aldosterone system 15,16 and the sympathetic pathway 17 in both pathologies. Structural cardiac abnormalities, such as cardiac fibrosis, 18 and increased left atrium and left ventricular hypertrophy, 19 also play a role in CKD and incident AF.…”
Section: Discussionmentioning
confidence: 99%